Portable skin analyzer based on smartphone - Chih-Chieh Wu; Shih-Jie Chou; Tai-Shan Liao; Chi-Hung Hwang (2013 IEEE International Symposium on Medical Measurements and Applications, 2013)
In this paper, a facial skin condition estimation function was developed on a smartphone. Skin image was captured by the image module of smartphone. An algorithm based on gradient operators was used to quantify the facial skin conditions by providing results as an index. Linear regression was applied to model the relationship between the index of skin conditions and the age of thirty subjects who ranged from 22 to 61. The result shows that the proposed skin age estimation function is able to measure one's skin age and has the potential to become a convenient skin inspection tool in cosmetic industry.